Information Systems, Technology and Management 6th International Conference, ICISTM 2012, Grenoble, France, March 28-30. Proceedings - Dua, Sumeet; Gangopadhyay, Aryya; Thulasiraman, P.; Straccia, Umberto; Shepherd, Michael; Stein, Benno (Communications in Computer and Information Science,, 2012)
This book constitutes the refereed proceedings of the 6th International Conference on Information Systems, Technology and Management, ICISTM 2012, held in Grenoble, France, in March 2012. The 38 revised papers were carefully reviewed and selected from 85 submissions. The papers are organized in topical sections on information systems; information technology; information management; business intelligence; management science and education; applications; workshop on program protection and reverse engineering.